PENGARUH MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PADA SATPOL PP KOTA SURAKARTA - Naibaho, Lancer S (-)
The purpose of this study is to examine the effect of work motivation and transformational leadership style on employee performance with satisfaction as intervening variable Satpol PP Kota Surakarta. The result of t test that is Motivation have positive and significant effect to Job Satisfaction, Transformational Leadership Style have positive and insignificant effect on Job Satisfaction. Transformational Leadership Style, Motivation and Job Satisfaction have positive and significant effect on Performance Value of R2 square total is 0,7225 which means employee performance variable explained by transformational leadership style and motivation with satisfaction as interverning variable equal to 72,25% and the rest equal to 27,75% Described other factors outside the research model. Effect of the most effective and dominant variable in order to improve the performance of Human Reusource on Satpol PP Surakarta is a variable of Â transformational leadership style. Â  Keywords: Motivation, transformational leadership style, job satisfaction, employee performance